2002
DOI: 10.1051/0004-6361:20021296
|View full text |Cite
|
Sign up to set email alerts
|

Normal modes of magnetic flux tubes and dissipation

Abstract: Abstract. Wave propagation in a zero-β magnetic flux tube with a discontinuous Alfvèn speed at its surface is considered. The problem is reduced to solving a wave equation for the projection of the magnetic perturbation along the axis of the cylinder. The mathematical formalism is identical with that for the propagation of electromagnetic waves in optical fibers with a varying index of refraction in the cross section of the fiber. The dispersion relation is solved in its full generality and three wave numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This is a particular form of other well-known dispersion relations (Edwin & Roberts 1983;Cally 1986;Karami et al 2002).…”
Section: Analytical Solutionmentioning
confidence: 84%
“…This is a particular form of other well-known dispersion relations (Edwin & Roberts 1983;Cally 1986;Karami et al 2002).…”
Section: Analytical Solutionmentioning
confidence: 84%
“…The coefficients ε, β, γ and ɛ are determined by the boundary conditions. From both Karami et al (2002) and Erdélyi & Carter (2006), the necessary boundary conditions are that: at the boundaries r = a and r = R , both the total Lagrangian pressure and δ v r should be continuous. These conditions yield to the dispersion relations for surface, m 2 0 > 0, and hybrid, m 2 0 < 0, modes which are same as the results obtained by Erdélyi & Carter (2006) in equations (28a) and (28b), respectively.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…They found that the existence of inhomogeneities in the form of structuring of the magnetic field enables loops to act as wave guides for a variety of different modes. Karami, Nasiri & Sobouti (2002) used the model of Edwin & Roberts (1983), and solved numerically the dispersion relation for each mode in its full generality. They obtained that in the presence of weak viscous and ohmic dissipations, the damping rate is inversely proportional to the Reynolds and Lundquist numbers, R and S , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…See, e.g., Karami et al (2002) and Safari et al (2006) for details. Let us also emphasize that the present form of Eq.…”
Section: Equations Of Motionsmentioning
confidence: 99%